Long-term Effects of Remote Ischemic Preconditioning on Kidney Function in High-risk Cardiac Surgery Patients: Follow-up Results from the RenalRIP Trial. (May 2017) - Zarbock, Alexander; Kellum, John A.; Van Aken, Hugo; Schmidt, Christoph; Küllmar, Mira; Rosenberger, Peter; Martens, Sven; Görlich, Dennis; Meersch, Melanie
Abstract : Background: In a multicenter, randomized trial, the authors enrolled patients at high-risk for acute kidney injury as identified by a Cleveland Clinic Foundation score of 6 or more. The authors enrolled 240 patients at four hospitals and randomized them to remote ischemic preconditioning or control. The authors found that remote ischemic preconditioning reduced acute kidney injury in high-risk patients undergoing cardiac surgery. The authors now report on the effects of remote ischemic preconditioning on 90-day outcomes. Methods: In this follow-up study of the RenalRIP trial, the authors examined the effect of remote ischemic preconditioning on the composite endpoint major adverse kidney events consisting of mortality, need for renal replacement therapy, and persistent renal dysfunction at 90 days. Secondary outcomes were persistent renal dysfunction and dialysis dependence in patients with acute kidney injury. Results: Remote ischemic preconditioning significantly reduced the occurrence of major adverse kidney events at 90 days (17 of 120 [14.2%]) versus control (30 of 120 [25.0%]; absolute risk reduction, 10.8%; 95% CI, 0.9 to 20.8%; P = 0.034). In those patients who developed acute kidney injury after cardiac surgery, 2 of 38 subjects in the remote ischemic preconditioning group (5.3%) and 13 of 56 subjects in the control group (23.2%) failed to recover renal function at 90 days (absolute risk reduction, 17.9%; 95% CI, 4.8 to 31.1%; P = 0.020). Acute kidney injury biomarkers were also increased in patients reaching the major adverse kidney event endpoint compared to patients who did not. Conclusions: Remote ischemic preconditioning significantly reduced the 3-month incidence of a composite endpoint major adverse kidney events consisting of mortality, need for renal replacement therapy, and persistent renal dysfunction in high-risk patients undergoing cardiac surgery. Furthermore, remote ischemic preconditioning enhanced renal recovery in patients with acute kidney injury. Abstract : Remote ischemic preconditioning significantly reduced the 3-month incidence of a composite endpoint major adverse kidney event consisting of mortality, need for renal replacement therapy, and persistent renal dysfunction in high-risk patients undergoing cardiac surgery.